Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter - Oliveira, Letícia A. De; Ferreira, Wellington D.; Inez, Tiago G.; Hermes, Marcel G. (Zootaxa, 2017)
Males of Minixi brethesi (Bertoni, 1927) and Minixi tricoloratum (Zavattari, 1911) are described for the first time. The synonymy of Alphamenes insignis loquax Giordani Soika, 1978 under Alphamenes richardsi Giordani Soika, 1978 is proposed. A new way to separate females of Alphamenes usitatus (Fox) from similar species is presented. An updated identification key is presented for the described species of Alphamenes Van der Vecht, 1977.